Electrochemical Sensor for Dopamine Based on Electropolymerized Molecularly Imprinted Poly-aminothiophenol and Gold Nanoparticles. (2017) - Ciui, Bianca; Tertis, Mihaela; Florea, Anca; Hosu, Oana; Peia, Diana; Sandulescu, Robert; Cristea, Cecilia
Abstract: An electrochemical MIP–based sensor has been developed for the sensitive and selective detection of dopamine which plays the role of the template, being a biomarker with implication in numerous neurological diseases. The electrochemical and morphological characterization of the sensor was performed by microscopy, electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and differential pulse voltammetry (DPV).